Interventional Ischemic Stroke Treatment – A (R)evolution - Friedrich, B.; Gawlitza, M.; Fahnert, J.; Quäschling, U.; Kahn, T.; Lobsien, D.; Hoffmann, K.-T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
In recent years ischemic stroke caused by an intracranial vessel occlusion has become a treatable disease. Over decades intravenous thrombolysis by recombinant tissue plasminogen activator was the only accepted causal treatment of ischemic stroke supported by the results of randomized, controlled trials. However, there has been continuous development of endovascular treatment strategies over recent years. Today there are 5 prospective, randomized multicenter studies showing the highly significant superiority of endovascular, mechanical recanalization over intravenous thrombolysis in cases of acute occlusion of an intracranial vessel of the anterior circulation. In all those studies endovascular treatment resulted in a tremendous increase in functional independence together with a reduction of mortality without a significant increase in complications. This article reviews the developments resulting in the current data and gives an overview of the present studies focusing on endovascular stroke treatment.Key Points:• In the last 20 years ischemic stroke due to an main stem occlusion has become a potentially treatable disease.• Several in 2015 published randomized Multicentener trials could prove the superiority of endovascular, mechanical recanalization over i.v. thrombolysis alone.•  Acute ischemic stroke due to a main stem occlusion should be treated with swift endovascular stent-retriever based recanalization in specialized neurovascular centers.Citation Format:• Friedrich B, Gawlitza M, Fahnert J et al. Interventional Ischemic Stroke Treatment – A (R)evolution. Fortschr Röntgenstr 2016; 188: 1 – 9
Keywords: brain; angiography; ischemia/infarction